Estratégias competitivas genéricas e desempenho econômico-financeiro das operadoras e seguradoras de plano de saúde - Vanderson Ribeiro Gonçalves (2022)
The research presented in this dissertation aimed to analyze the generic strategies adopted by health insurance providers (OPS) in the Brazilian market and the relationship between that estrategies and the economic-financial performance in the period from 2011 to 2021. To this end, the following specific objectives were proposed and fulfilled: (a) Identify Porter's generic strategies adopted by Brazilian OPS; (b) to compare the long-term economic and financial performance of the OSPs based on the generic strategy adopted; (c) to measure the effect of adopting such strategies on the current economic and financial performance of these organizations; and (c) discuss the role of adopting such strategies for competitive advantage for OSPs of different modalities. For the development of this descriptive, correlational and quantitative research, secondary financial and operational data made publicly available by the National Supplementary Health Agency (ANS) were obtained. Such data were collected from OPS with active registration in the ANS between the years 2011 and 2021 belonging to the following modalities: medical cooperative, philanthropy and group medicine. Five metrics were proposed to classify OPS according to one of the following strategies: cost leadership, differentiation, hybrid or stuck in the middle. Return on assets (ROA), return on equity (ROE) net profit margin and growth rate were also used as performances metrics. For data processing and analysis, the following techniques were used: descriptive statistics, factor analysis, Mann-Whitney U test and regression with panel data. It was found that OPS had difficulty in effectively adopting a generic strategy and a preference for adopting a cost leadership strategy among those that adopted one. It is also concluded that adopting a strategy implies superior performance in the long term, depending on which aspect of performance is being considered, but in many aspects no performance differences were observed between the strategies adopted. A similar result is observed for current performance.